2021
DOI: 10.1136/tsaco-2021-000686
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the delays in adequate thromboprophylaxis after TBI

Abstract: BackgroundWe sought to compare enoxaparin dosing for venous thromboembolism (VTE) prophylaxis in trauma patients with and without traumatic brain injury (TBI) to better understand the time and dose required to reach target anti-Xa levels. Our hypothesis was that patients with TBI have significant delays in the initiation of adequate pharmacological prophylaxis and require a higher enoxaparin dose than currently recommended.MethodsThe medical records of trauma patients who received enoxaparin dosing based on an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 37 publications
(40 reference statements)
0
10
0
Order By: Relevance
“…Dose adjustment based on anti-Xa alone may inadequately reduce VTE rates because waiting for the first anti-Xa level delays dose optimization. Studies have demonstrated that when dosing VTEp is based on anti-Xa, an additional 3.5 days elapses prior to achieving dose adequacy 43 ; this delay may explain why VTE rates are not necessarily reduced with an anti-Xa–based LMWH dosing strategy. Alternatively, this finding may suggest that anti-Xa levels simply describe a patient's thrombotic state at a given time, and are not a reliable indicator of VTEp over the entire episode.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dose adjustment based on anti-Xa alone may inadequately reduce VTE rates because waiting for the first anti-Xa level delays dose optimization. Studies have demonstrated that when dosing VTEp is based on anti-Xa, an additional 3.5 days elapses prior to achieving dose adequacy 43 ; this delay may explain why VTE rates are not necessarily reduced with an anti-Xa–based LMWH dosing strategy. Alternatively, this finding may suggest that anti-Xa levels simply describe a patient's thrombotic state at a given time, and are not a reliable indicator of VTEp over the entire episode.…”
Section: Discussionmentioning
confidence: 99%
“…blinded to the studies being assessed, with disagreements resolved by consensus or third-party adjudication. Included nonrandomized studies were assessed for quality using the Methodological Index for Nonrandomized Studies (MINORS) 43 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are challenges with initiating and dosing chemoprophylaxis in trauma patients with traumatic brain injury, spinal injury, and solid organ injuries even with current regimens. [37][38][39] Establishing that oral agents are safe in these specific injuries and in patients with multiple injury will require further studies.…”
Section: Future Directionsmentioning
confidence: 99%
“…The heterogeneity of injury patterns and bleeding risk after major trauma make generalized recommendations regarding the optimal novel chemoprophylactic strategy difficult to define and implement. There are challenges with initiating and dosing chemoprophylaxis in trauma patients with traumatic brain injury, spinal injury, and solid organ injuries even with current regimens 37–39 . Establishing that oral agents are safe in these specific injuries and in patients with multiple injury will require further studies.…”
Section: Future Directionsmentioning
confidence: 99%